Infecção natural pelo vírus da diarreia viral bovina (BVDV) em bovinos de corte no Estado do Pará - Viana, Rinaldo Batista; Fava, Claudio Del; Rezende, Marcus Luciano Guimarães; Pereira, Washington Luiz Assunção; Monteiro, Bruno Moura; Albuquerque, Rodrigo dos Santos; Pituco, Edviges Maristela (Acta Scientiae Veterinariae, 2017)
Background: Bovine viral diarrhea virus (BVDV) is a pathogen that causes great economic losses in dairy and beef herds. The main disturbances caused by this virus are related to abortion, fetal malformation and mummification, and the birth of weak calves. In addition, this disease may result in persistently infected animals, as well as individual immune tolerance to the virus. However, the symptoms are nonspecific and variable, and dependent on the age of affected animal. The objective of the present study was to report three cases with clinical signs of BVDV infection, with subsequent confirmation of the diagnosis by reverse transcription - polymerase chain reaction technique (RT-PCR). Cases: In a beef production farm located at the state of Para, Brazil, three animals presented severe diarrhea; the feces were liquefied and greenish-yellow in color; crusted lesions were visible and scattered over various parts of the animals’ bodies, including the muzzle, nostrils, periauricular region, and hooves; the tongue mucosa was undergoing an intense desquamation process. One of the affected animals, a 6-month-old calf, was euthanized following the recommendations of the “Brazilian guide to good practices for animal euthanasia” of the Ethics, Bioethics and Animal Welfare Committee / Federal Council of Veterinary Medicine. After euthanasia, this calf was necropsied and some of its organs, including the tongue and skin, were sent to the Biological Institute of Sao Paulo State for histopathology examination (HE) and identification and isolation of the virus. Positive samples for the presence of BVDV were diagnosed by RT-PCR, confirming the suspicion and explaining the signs observed in that animal and reported in other dead animals of the farm. Because RT-PCR was performed in ulcerative lesions present in the tongue, negative reactions were detected for bovine herpesvirus (BoHV) and positive reactions for BVDV. The cutaneous tissue was marked with lymphocytic infiltration, observed in both epidermis and dermis, which refers to crusted lesions distributed in several regions of the animal’s body. In the lungs, we observed rare areas of emphysema and marked lymphocytic interstitial pneumonia with hemorrhagic spots, correlated with symptoms of respiratory disease. Also, marked renal damage and spleen lesions were identified, indicating glomerulonephritis and lymphocytic splenitis. Discussion: This study evidenced the occurrence of BVDV in two calves and one adult animal, which is in agreement with the described higher incidence of symptomatic infection in young animals. Clinical signs of severe greenish-yellow diarrhea and crusted lesions distributed throughout several regions of the animals’ bodies, including the muzzle, nostrils, periauricular region, and hooves were described, with intense tongue epithelium desquamation, which is a particular and characteristic symptom of Mucosal Disease - the classical form of the physiopathogeny caused by bovine viral diarrhea virus. The clinical findings of severe diarrhea are possibly related to the histopathological results, which showed hyaliniza- tion of the intestinal mucosa and rare mononuclear cells in the liver nodules. Pulmonary histopathological findings of rare areas of lymphocytic interstitial pneumonia, severe emphysema, and hemorrhagic foci refer to respiratory diseases. Based on the clinical signs and laboratory findings, we conclude that the affected animals showed classic symptoms of bovine viral diarrhea. This diagnosis highlights the presence of the disease in cattle raised in the state of Para, Brazil.